IMPLEMENTASI METODE ROTE LEARNING DALAM PEMBELAJARAN ILMU TAJWID - Ramhadi Ramhadi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2020)
The present study aimed at finding out the portrayal of rote learning method implementation which was applied by the coaches of TPQ al-Barokah in Kampung Melayu Village, Rejang Lebong, Bengkulu. This study used a qualitative approach. The data were gathered by means of observation and interview techniques. After the data were collected, the data were analyzed using phases referring to Miles, Huberman, and Saldana comprising data condensation, data display, and drawing conclusion. The findings of this study concluded that the rote learning method for Tajwid learning was considered very effective to be applied, and its merit was evident in students’ competence in the recitation of Qur’an at TPQ al-Barokah. Their competence was seen when they were re-examined by their Qur’anic coaches, and they could provide examples of Tajwid’s application in the Qur-an properly and correctly.